THE BUSINESS MODEL CANVAS TO DEVELOP ENTREPRENEURIAL MINDSET IN ONLINE LEARNING - Nurseto, Tejo; Sulasmi, Sulasmi; Alwi, Ahmad Chafid (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This article aims to describe the implementation of the Business Model Canvas (BMC) in developing an entrepreneurial mindset (EM) within an online learning environment. This study employed a descriptive observational analytic method within a one-shot case study design. The subjects were 29 Economic Education students from the Faculty of Business and Economics at Yogyakarta State University who participated in an entrepreneurship practicum course. Data were analyzed using descriptive analysis. The results indicate that (1) The implementation of BMC effectively develops an entrepreneurial mindset. (2) The students' entrepreneurial mindset following the BMC online learning is characterized by the following indicators: motivation (66%), intention (52%), decision-making (48%), job experience (45%), friendly personality (41%), risk-taking and effective communication (38%), organizational experience (14%), active in organizing (10%), business experience (9%), and leadership (7%). (3) The entrepreneurial mindset of students who have participated in BMC-based learning is categorized as high (72.41%) and medium (27.59%).